2020
DOI: 10.1126/sciadv.aay9842
|View full text |Cite
|
Sign up to set email alerts
|

Wireless battery-free wearable sweat sensor powered by human motion

Abstract: Wireless wearable sweat biosensors have gained huge traction due to their potential for noninvasive health monitoring. As high energy consumption is a crucial challenge in this field, efficient energy harvesting from human motion represents an attractive approach to sustainably power future wearables. Despite intensive research activities, most wearable energy harvesters suffer from complex fabrication procedures, poor robustness, and low power density, making them unsuitable for continuous biosensing. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
235
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 431 publications
(277 citation statements)
references
References 56 publications
0
235
0
Order By: Relevance
“…[6,79] The as-obtained dynamic changes in Na + levels showed a similar trend to previously reported wearable sweat sensors. [3,70,[80][81][82] To demonstrate the stretchable performance of wearable sensors for on-body sweat measurements, a volunteer wearing a sensor device performed a seated rowing exercise during stationary cycling (Figure 6d and Movie S1, Supporting Information). The sensor attached to the arm was continuously stretched and relaxed according to the upper body resistance training.…”
Section: (8 Of 12)mentioning
confidence: 99%
“…[6,79] The as-obtained dynamic changes in Na + levels showed a similar trend to previously reported wearable sweat sensors. [3,70,[80][81][82] To demonstrate the stretchable performance of wearable sensors for on-body sweat measurements, a volunteer wearing a sensor device performed a seated rowing exercise during stationary cycling (Figure 6d and Movie S1, Supporting Information). The sensor attached to the arm was continuously stretched and relaxed according to the upper body resistance training.…”
Section: (8 Of 12)mentioning
confidence: 99%
“…Song et al. developed a power management and biosensors system on a flexible printed circuit board, which could transmit data to a mobile phone in real time 18 . In the future, efforts are needed to improve the generator's output, enhance the efficiency of the power management circuit, and develop suitable application systems.…”
Section: Human‐body Motions Charged Energy Storage Devicesmentioning
confidence: 99%
“…The power, current, or voltage outputs of human body energy harvesters are proportional to the intensity of human physiological signals such as frequency of human motions, 14 concentrations of lactate/glucose in sweat/blood, 15 or temperature of the human body 16 . Another way is to utilize a form of human‐body energy harvester to provide energy for other biological signals or external stimuli, such as using the triboelectric nanogenerators (TENGs) to power a temperature sensor and chemical sensors 17,18 . More specifically, the human‐body energy harvesters can be possibly fabricated into a self‐sustainable implantable device, to eliminate the requirement of the recharging process, and avoid further surgery for changing the energy source that would impart suffering, high cost, and risk to wearers 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Wearable self-powered platforms satisfy the REASSURED requirement for real-time, easy sample collection and being user-friendly. For example, Song et al [ 115 ] have recently reported on the development of a self-powered wearable system consisting of a wearable freestanding-mode TENG, low-power wireless sensor circuitry, and a microfluidic sweat sensor patch on a single flexible printed circuit board platform to dynamically monitor and quantify key sweat biomarkers (e.g., pH and Na + ). Similarly, colorimetric responses in functionalized porous substrates on soft, skin-mounted sensors electronics can yield chemical information, such as the pH of sweat, and further enable simple quantitative assays [ 126 ].…”
Section: Challenges and Future Outlookmentioning
confidence: 99%